Rancang Bangun Sistem Penerimaan Siswa Baru Pada LBB Chemistry Jakarta - Sinun, Ahmad; Fatma Utami, Anastasia Siwi; Prasetyo, Feri; Palasara, Nicodias; Khairullah, Mochamad Isha (INFORMATION MANAGEMENT FOR EDUCATORS AND PROFESSIONALS : Journal of Information Management, 2024)
Tutoring institutions are currently one of the choices of parents to improve their children's academic achievement and many are still in the process of accepting new students that have not been automated. Therefore, a new web-based student admission information system at an institution called Chemistry is the right solution to overcome these obstacles so that students who want to register can easily register and tutoring institutions can also easily carry out the selection process, data verification, and processing of student data. This study used a qualitative methodology, including by observing, interviewing, and studying the literature. With the creation of this information system, it is hoped that there will be an increase in efficiency and convenience in registering new students. The use of the Laravel framework in its design is also expected to make the system reliable, secure and structured. The SDLC (System Development Life Cycle) method with the Waterfall model is intended so that the development of this information system can run in a structured manner, is easy to used too, and is understood later for further development.